2018
DOI: 10.1177/0309364618774193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an epicondylitis bandage with a wrist orthosis in patients with lateral epicondylitis

Abstract: Epicondylitis bandage and hand-wrist resting orthosis are equally effective treatment options for lateral epicondylitis-induced pain, functional status, muscle strength, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…The meta-analysis (Figure 3(a)) showed a small-to-moderate improvement in favor of the wrist splint group on pain scores (SMD 0.35; 95% CI −0.07 to 0.76) with moderate statistical heterogeneity (heterogeneity χ 2 = 9.08 (p = 0.059) I 2 = 55.9%). However, only Akkurt et al 29 showed a small improvement in favor of a counterforce brace group at six weeks (SMD −0.07; 95% CI −0.50 to 0.36). The trial by Forogh et al 32 used a new orthosis with a covered forearm in the comparison group.…”
Section: Counterforce Brace Versus Wrist Splintmentioning
confidence: 94%
See 3 more Smart Citations
“…The meta-analysis (Figure 3(a)) showed a small-to-moderate improvement in favor of the wrist splint group on pain scores (SMD 0.35; 95% CI −0.07 to 0.76) with moderate statistical heterogeneity (heterogeneity χ 2 = 9.08 (p = 0.059) I 2 = 55.9%). However, only Akkurt et al 29 showed a small improvement in favor of a counterforce brace group at six weeks (SMD −0.07; 95% CI −0.50 to 0.36). The trial by Forogh et al 32 used a new orthosis with a covered forearm in the comparison group.…”
Section: Counterforce Brace Versus Wrist Splintmentioning
confidence: 94%
“…After screening based on title and abstract, 79 studies were selected for full-text evaluation. Finally, 17 RCTs 3, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] were considered in the final synthesis. However, one study 3 was removed from the meta-analysis due to categorical data.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there are wrist orthoses which should reduce the overload on the wrist extensors. However, the reported effects of those orthoses in LE are heterogeneous and there are limited studies that compare different orthotic devices against each other or a placebo with a high evidence level [ 18 20 ]. There are no studies that evaluate the effect of a dynamic wrist orthoses.…”
Section: Introductionmentioning
confidence: 99%